Divergence between new and existing FDI in times of sustained inflation post the COVID-19 pandemic: The case of a subnational economy in the U.S. - Roxana Wright; Chen Wu (Economies, 2025)
The relationship between inflation and foreign direct investment (FDI) is not clear-cut in theory. In the U.S., rising inflation coupled with increased economic recovery boosted FDI immediately after the COVID-19 pandemic but suppressed it afterwards. To shed light on the relationship between inflation and the resulting contractionary monetary policy and FDI, three key propositions were put forth for investigation. The propositions rely on relevant scientific literature showing that (1) although the connection between FDI and inflation is complex, a high and sustained inflation depresses incoming FDI due to increases in uncertainty and guarding government policies; (2) there exist significant location-based differences in how this connection manifests; and (3) high inflation and subsequent policies motivate FDI-related strategic action. Thus, we propose that new FDI is expected to be negatively affected by the rising entry cost associated with an inflationary economy that adopts anti-inflationary policies. Second, there exists heterogeneity in the effects of inflation on new FDI across subnational economies with various local characteristics. Third, existing FDI demonstrates strategic actions and expansion at the subnational location and beyond, even under inflationary pressure. We employ a positive comparative analysis based on descriptive statistics and qualitative interpretation of data to examine the status and activities of both new FDI (using subnational aggregated data) and existing foreign businesses (using firm-level data) in the state of New Hampshire during the recent inflation surge of 2022-2023. Our analysis provides empirical evidence supporting our propositions. Key implications are that, during challenging times of inflation and recovery, business leaders and economic development professionals should anticipate strategic actions to expand markets, products, operations, and partnerships. Leaders and professionals should act to take advantage of business actions outside the subnational location, as more companies look to strengthen and diversify their national and international networks.
Keywords: 330; foreign direct investment; inflation; subnational economy; business strategy